THE GROWTH FACTOR AND BULK HYGROSCOPICITY OF ATMOSPHERIC SOOT OF URBAN AEROSOLS - Akpootu, Davidson Odafe; Aruna, S.; Bello, G.; Aminu, Z.; Isah, A. K.; Umar, M.; Badmus, T. O.; Alaiyemola, S. R.; Abdulsalam, M. K.; Meseke, N. O.; Abdullahi, Z. (FUDMA JOURNAL OF SCIENCES, 2023)
Aerosols within urban atmosphere can be composed of water-soluble aerosols from industrial emissions, insoluble and soot from biomass and bio-fuel emissions respectively. In this study, simulation was carried out using Optical Properties of Aerosols and Clouds (OPAC) to model the hygroscopic growth factor and bulk hygroscopicity of Soot at spectral range of 0.25 to 1.00 mm for eight different relative humidities. The results in this study revealed that the aerosol hygroscopic growth factor increases with relative humidity (RH) while the bulk hygroscopicity decreases with increase in RH from 50-99% RHs. The aerosol hygroscopic growth factor increases with increase in RH while the bulk hygroscopicity decreases with increase in RH for the number, volume and mass ratios. The aerosol growth factor revealed that the mixture is barely hygroscopic, less hygroscopic and more hygroscopic from 50 – 80% RH, 90 – 95% RH and 98 – 99% RH respectively for the number mix ratio. The aerosol growth factor revealed that the mixture is less hygroscopic, more hygroscopic and most hygroscopic from 50 – 80% RH, 90 – 95% RH and 98 – 99% RH respectively for the volume and mass mix ratios. The bulk hygroscopicity ranges between 0.02007 to 0.09456 for the number mix ratio from model 1 to model 3, the bulk hygroscopicity ranges between 0.13596 to 0.32956 for the volume mix ratio from model 1 to model 3 while the bulk hygroscopicity ranges between 0.12831 to 0.29925 for the mass mix ratio from model 1 to model 3.
Keywords: bulk hygroscopicity; hygroscopic growth factor; OPAC; relative humidity; soot